An illustrative understanding of strengthening the stability and efficiency of perovskite solar cells: utilization of the perovskite-constructed polymer hybrid system, PHQACl-CN. Issue 46 (21st November 2022) - Ingabire, Providence Buregeya; Gu, Ningxia; Lei, Ning; Song, Lixin; Chen, Xiang; Zhang, Pengyun; Chen, Shouwen; Du, Pingfan; Xiong, Jie
Abstract : Integrating a proper amount of polymer hybrid of quaternary ammonium chloride functionalized graphitic carbon nitride (PHQACl-CN) in the perovskite leads to positive adjustments in the morphology of the treated perovskite films and boosts the PSC device performance. Abstract : The nature of perovskite films ensures the viable concern of perovskite solar cells (PSCs), leading to both satisfactory stability and adequate photovoltaic performance. In this work, a polymer hybrid of quaternary ammonium chloride functionalized graphitic carbon nitride (PHQACl-CN), a promising material with a structure consisting of a cationic ammonium group and an anionic chloride group, is integrated into perovskite. A satisfactory amount of PHQACl-CN in the perovskite favors good crystal morphology, and represses the generation of surface or point defects by sequestering counter ions and reducing ion movement. Experiments reveal that PHQACl-CN establishes strong hydrogen bonding interactions with perovskite, reducing charge carrier recombination. As a consequence, perovskite films with enlarged grain size and lacking pinholes are achieved, which show enhanced performance and stability. The most efficient PSC processed with PHQACl-CN3 shows a PCE of 18.21% with improved stability, where 82% of the original efficiency is maintained after 320 h of shelf storage, and over 73% of the original efficiency is retained after a continuous 200 h of thermal handling at 85 °C under moisture levels of 45–50%RH in air. The PHQACl-CN-patterned perovskite films are encouraging for utilization in PSCs.